Critical area identification and dynamic process simulation for landslide hazard chain formation in the upstream Jinsha River - Song, Yixian; Deng, Hongyan; Tang, Chenxiao; Li, Bokai (Frontiers in Earth Science, 2023)
The upper reaches of the Jinsha River, with their complex terrain and active tectonic movements, are vulnerable to landslide-induced hazard chain events, which endanger the safety of residents and infrastructure construction. Based on the analyses of the development background of the hazard chain in the Jinsha River upstream, five factors, including the lithology, distance to faults, distance to rivers, peak ground acceleration, and slope degree, were selected to identify the critical areas prone to landslides, and the principal component and grey correlation analyses were then conducted to determine the contributions of the different factors. Based on ArcGIS, the study zone was categorized into three classes of landslide susceptibility: high, moderate, and low. The identification of the critical target areas for landslide hazard chain formation achieved satisfactory accuracy. The high susceptibility areas concentrate along the Jinsha River. The dynamic process of a typical landslide that was selected from the high-susceptibility areas was numerically simulated using Openlisem. The high-precision Baige landslide data of the study area were used to calibrate the practicality of the input mass parameters, such as cohesion, internal friction angle, D50, and D90. Then, the movement and accumulation process of the typical landslide were numerically simulated with the verified data. The entire landslide accumulation covers an area of 0.45 km^2, with a length of 1600 m and a width of 270 m. Thus, the Openlisem model, which combines mass, topography, and landcover parameters, is feasible for the numerical simulation of the dynamic process of landslides. The prediction about the dynamic process and accumulation morphology of landslides can provide a reference for the formation process and mechanism of landslide-induced hazards chain in the upper Jinsha River.